Sex and age differences in hospitalized pediatric traumatic brain injury. Issue 9 (30th September 2019) - Zhang, Fang; Huang, Lihong; Singichetti, Bhavna; Li, Huiling; Sullivan, Lindsay; Yang, Jingzhen Ginger
Abstract: Background: The aim of this study was to investigate the epidemiological characteristics of pediatric traumatic brain injury (TBI) requiring hospitalization in Chinese children ≤17 years of age according to sex and age group. Methods: This study retrospectively analyzed pediatric TBI inpatient data obtained via electronic health records from one children's hospital in China. Patients aged ≤17 years admitted to the hospital due to TBI between 1 January 2013 and 31 December 2015 were identified using International Classification of Diseases (ICD) ‐9 and ICD‐10 codes. The demographic, injury, and hospitalization characteristics were analyzed by sex and age groups. Results: The subject consisted of 1, 087 pediatric TBI patients admitted to the hospital (61.5% boys). The highest proportion of hospitalization was observed in the 1–3 years age group. For both boys and girls, the most common diagnosis was "traumatic epidural hematoma" and the leading mechanism of TBI was "fall". The median length of hospital stay was 8.5 days and the median hospitalization cost was 7, 977.4 Chinese yuan (approximately US 1, 140). Conclusions: Boys and children aged 1–3 years incurred more pediatric TBI requiring hospitalization than their counterparts. Prevention of falls, the most common injury mechanism in both boys and girls, is an important strategy to reduce pediatric TBI and related hospitalizations.